If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(x + 5)(x + -10) = 7 Reorder the terms: 3(5 + x)(x + -10) = 7 Reorder the terms: 3(5 + x)(-10 + x) = 7 Multiply (5 + x) * (-10 + x) 3(5(-10 + x) + x(-10 + x)) = 7 3((-10 * 5 + x * 5) + x(-10 + x)) = 7 3((-50 + 5x) + x(-10 + x)) = 7 3(-50 + 5x + (-10 * x + x * x)) = 7 3(-50 + 5x + (-10x + x2)) = 7 Combine like terms: 5x + -10x = -5x 3(-50 + -5x + x2) = 7 (-50 * 3 + -5x * 3 + x2 * 3) = 7 (-150 + -15x + 3x2) = 7 Solving -150 + -15x + 3x2 = 7 Solving for variable 'x'. Reorder the terms: -150 + -7 + -15x + 3x2 = 7 + -7 Combine like terms: -150 + -7 = -157 -157 + -15x + 3x2 = 7 + -7 Combine like terms: 7 + -7 = 0 -157 + -15x + 3x2 = 0 Begin completing the square. Divide all terms by 3 the coefficient of the squared term: Divide each side by '3'. -52.33333333 + -5x + x2 = 0 Move the constant term to the right: Add '52.33333333' to each side of the equation. -52.33333333 + -5x + 52.33333333 + x2 = 0 + 52.33333333 Reorder the terms: -52.33333333 + 52.33333333 + -5x + x2 = 0 + 52.33333333 Combine like terms: -52.33333333 + 52.33333333 = 0.00000000 0.00000000 + -5x + x2 = 0 + 52.33333333 -5x + x2 = 0 + 52.33333333 Combine like terms: 0 + 52.33333333 = 52.33333333 -5x + x2 = 52.33333333 The x term is -5x. Take half its coefficient (-2.5). Square it (6.25) and add it to both sides. Add '6.25' to each side of the equation. -5x + 6.25 + x2 = 52.33333333 + 6.25 Reorder the terms: 6.25 + -5x + x2 = 52.33333333 + 6.25 Combine like terms: 52.33333333 + 6.25 = 58.58333333 6.25 + -5x + x2 = 58.58333333 Factor a perfect square on the left side: (x + -2.5)(x + -2.5) = 58.58333333 Calculate the square root of the right side: 7.653975002 Break this problem into two subproblems by setting (x + -2.5) equal to 7.653975002 and -7.653975002.Subproblem 1
x + -2.5 = 7.653975002 Simplifying x + -2.5 = 7.653975002 Reorder the terms: -2.5 + x = 7.653975002 Solving -2.5 + x = 7.653975002 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = 7.653975002 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = 7.653975002 + 2.5 x = 7.653975002 + 2.5 Combine like terms: 7.653975002 + 2.5 = 10.153975002 x = 10.153975002 Simplifying x = 10.153975002Subproblem 2
x + -2.5 = -7.653975002 Simplifying x + -2.5 = -7.653975002 Reorder the terms: -2.5 + x = -7.653975002 Solving -2.5 + x = -7.653975002 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '2.5' to each side of the equation. -2.5 + 2.5 + x = -7.653975002 + 2.5 Combine like terms: -2.5 + 2.5 = 0.0 0.0 + x = -7.653975002 + 2.5 x = -7.653975002 + 2.5 Combine like terms: -7.653975002 + 2.5 = -5.153975002 x = -5.153975002 Simplifying x = -5.153975002Solution
The solution to the problem is based on the solutions from the subproblems. x = {10.153975002, -5.153975002}
| 79-17/8 | | 8=-3x+4x+1 | | 3(c-5)+4c(c-5)= | | 11x-7x=4 | | 3(x-4)=2(5x-11) | | 6x-3(1)=0 | | -7x-9=54 | | 4x+48=-2x | | 5x-15=-2x+20 | | 2x-6=-4x+42 | | x=5::3:2.5 | | 6(0)-3y=0 | | 4x-12=-4x+28 | | 3/2m-m=41/2m | | 10x+5x+45+90=360 | | 6x-2x=20 | | 7(8x-5)=77 | | 2(7c+2)= | | 5x-2x=3 | | 9x-30=-3(5x-6) | | -3+6x+6x= | | 4x^2-5x+19=0 | | xx-4x-12=0 | | 7/4(x)=-21 | | 17/24+16/24 | | 2(x-3)+2=5x-3(2+x) | | 4x^2+14x=368 | | 33/24 | | 4(x-3)+9x=-38 | | 5x+15/x^2+3x | | 10-(4y-4)=3-5y | | -9x+9(1)=0 |